Vergi hukuku bakımından uygulanan haciz işlemi üzerine mükellefin başvurabileceği hukuki bir yol: Tazminat davası - Yıldız, Bilge (İstanbul Kültür Üniversitesi / Lisansüstü Eğitim Enstitüsü / Kamu Hukuku Ana Bilim Dalı / Kamu Hukuku Bilim Dalı, 2021)
Mükellef tarafından vergi kanunlarına göre tespit edilen vergi borcununkanuni süresi içinde alacaklı vergi idaresine ödenmesi gerekmektedir. Mükellef tarafından bu hususa aykırı olarak hareket edildiği takdirde,vergi idaresinceAATUHK'de yer alan cebren tahsil yollarına başvurulabilir. AATUHK'de düzenlenen cebren tahsil yollarından biri, haciz yoluyla takiptir. Bazı durumlarda alacaklı vergi idaresince uygulanan haciz işlemi AATUHK'de düzenlenen usule aykırı olarak gerçekleştirilebilir ve bu işlem sebebiyle mükellefin zarara uğraması söz konusu olabilir. Bu durumda mükellef tarafından haciz işlemi sebebiyle uğranılan zararın giderilmesi amacıyla alacaklı vergi idaresi aleyhine tazminat davası açılabilir. İşbu çalışmada bu dava türüne giden süreç, davanın hukuki niteliği, esasa ve usule ilişkin şartları ve davanın sonuçları üzerinde durulacaktır. Çalışmadört bölümolup her bölümde doğruluğu herkesçe sabit olan konularla birlikte tartışmalı hususlara da değinilmiş, konuya ilişkin yargı kararlarından yararlanılmış ve uygulamadan örneklere yer verilmiştir.İlgili dava türüne uygulamada mükellefler tarafından çok sık başvurulmamakla birlikte başvurulsa dahi yargı makamlarının katı görüşleri sebebiyle sonuç alınmasıoldukça güçtür. Bu nedenle bahsi geçen dava türü işbu çalışma ile kapsamlı bir şekilde ele alınarak konuya hukuki bir katkıda bulunulması amaç edinilmiştir.

The tax that has to be paid by the taxpayer in accordance with the tax laws must be deposited to the cashier of the creditor tax administration within the legal period.Supposing that the taxpayer acts unlawfully for this matter,the tax administration may apply the compulsory collection methods specified in law on procedure for the collection of public receivables. One of the ways of compulsory collection regulated in the procedure for the collection of public receivables is attachment proceedings. In some cases, the attachment proceeding initiated by the creditor tax administration may be acted without due process of law regulated in the procedure for the collection of public receivables and the taxpayer may suffer by this transaction. In this case, in order to compensate for damages of attachment proceeding, the taxpayer can sue for damages against the tax administration. In this study, the process leading to this type of case, the legal nature of the case, the substantive and procedural conditions and the results of the case will be discussed. The subject of the study has been reviewed under four chapters; in each chapter, besides the subjects whose accuracy is valid for everyone, controversial issues are also mentioned, judicial decisions related to the subject are used and examples from practices are also pre'sented. Although the related type of case is not frequently applied by the taxpayers in practice, it is very difficult to get results due to the strict opinions of judicial authorities, even if it is sued. For this reason, it is aimed to make a legal contribution to the issue by adressing the mentioned type of the case comprehensively with this study.
A legal procedure that a taxpayer can follow on the attachment proceeding in terms of taxation law and legislation: Suit of damage
Keywords: Hukuk; Law